Extract having protease activity - Abd Manap, Mohd Yazid; Naderi, Nassim; Sipat, Abdullah; Idris, Yousif Mohamed Ahmed (2013)

(untitled)
The present invention discloses a composition comprising a proteinaceous extract of Streblus asper having substantially protease activity that degrades proteins by hyrolysis of peptide bonds. The proteinaceous extract of Streblus asper according to the present invention is suitable for us as a meat quality-imroving agent and a milk coagulant in food processing industries, as well as an additive in the manufacture of detergents.